Specific ICF training is needed in clinical practice: ICF framework education is not enough - Paltamaa, Jaana; van Lingen, Ellen; Haumer, Christine; Kidritsch, Anita; Aerts, Ingrid; Mutanen, Laura (Frontiers in Rehabilitation Sciences, 2024)
The use of a common language in interprofessional collaboration is essential. The World Health Organization's International Classification of Functioning, Disability and Health (ICF) has been identified as a unifying framework for interprofessional collaboration and the identification of client needs. Higher education institutions (HEIs) offer ICF framework education to students but is it enough to enable graduated professionals to implement the ICF in clinical work? In our experience, the ICF education provided by HEIs does not meet the requirements of clinical practice, which might be due to gaps in teaching ICF to students (education) and specific requirements for teaching ICF to professionals already working in rehabilitation (training). This paper discusses the need for the ICF training in practice and ways to address it. Although many rehabilitation center professionals had previously received ICF education provided by the HEIs, the rehabilitation centers felt the need to develop their own practical training materials that could be applied to their own environment. Overall, 18 different ICF-based materials were developed during the Erasmus+ project called INPRO to promote person-centered and interprofessional practice in the rehabilitation centers. The practical training using real cases was considered valuable. It could be further developed in cooperation with HEIs and vice versa. It could also be used to teach students, i.e., future colleagues. To deepen and broaden the integration of the different materials based on the ICF, it is important to continue the interactive discussion between HEIs and clinical practice, and between management and its staff.